2010
DOI: 10.1001/archinternmed.2010.342
|View full text |Cite
|
Sign up to set email alerts
|

Postmenopausal Hormone Use and the Risk of Nephrolithiasis

Abstract: Background Observational studies examining the role of estrogen in the risk of kidney stone formation have shown conflicting results. However, randomized trial evidence on nephrolithiasis risk with estrogen therapy in postmenopausal women is lacking. Methods We reviewed the incidence of nephrolithiasis in the Women’s Health Initiative estrogen-alone and estrogen plus progestin trials conducted at 40 US clinical centers. A total of 10 739 postmenopausal women with hysterectomy were randomized to receive 0.625… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 31 publications
0
19
0
1
Order By: Relevance
“…While Maalouf et al provided evidence that estrogen supplementation increases the risk for kidney stones in post-menopausal women [26], other studies demonstrate an inhibitory effect of female reproductive hormones [27,28]. Additionally, data regarding the potential mechanisms are inconsistent [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…While Maalouf et al provided evidence that estrogen supplementation increases the risk for kidney stones in post-menopausal women [26], other studies demonstrate an inhibitory effect of female reproductive hormones [27,28]. Additionally, data regarding the potential mechanisms are inconsistent [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Maalouf et al 46 analyzed the WHI database for kidney stones. We examined Maalouf et al's presentation of the data for the timing hypothesis and found that only the cohorts of women 6 to 10 years beyond the menopause and aged 60 to 64 had CIs of hazard ratio (HR) greater than 1 (Figs.…”
Section: The Role Of Eu-estrogenemia In Liver Function Diabetes Andmentioning
confidence: 99%
“…Newer studies have shown, by analyzing multiple regression, that there is a significant influence of age as well as a daily input of calcium, on the loss of bone mass in the patients with urolithiasis. Bone mass was significantly decreased in patients with urolithiasis compared to the control group (p< 0.001) and it was more conditioned by an older age, particularly in women in menopause ( 19 ). Reference data show that clinical and epidemiological research have shown that in older patients with urolithiasis, there is an increased bone disintegration and reduced mineral bone density (MBD) ( 20 , 21 ).…”
Section: Discussionmentioning
confidence: 94%